Inoculation Effect of N2-Fixer and P-Solubilizer into a Mixture of Fresh Manure and Phosphate Rock Formulated as Organonitrofos Fertilizer on Bacterial and Fungal Populations - Sutopo Ghani Nugroho; . Dermiyati; Jamalam Lumbanraja; Sugeng Triyono; Hanung Ismono (JOURNAL OF TROPICAL SOILS, 2013)
Microbial N2-fixer and P-solubilizer were innoculated in a mixture of fresh manure and phosphate rock formulated as an Organonitrophos fertilizer. The population dynamics of bacteria and fungi growing during the composting process were observed. The inoculation treatments consisted of: K = mixture of 20% phosphate rock and 80% of fresh manure + decomposers (control), N = mixture of 20% phosphate rock and 80% of fresh manure + decomposers + N2-fixer (Azotobacter and Azospirillum sp.) , P = mixture of 20% phosphate rock and 80% of fresh manure + decomposers + P-solubilizer (A. niger and P. fluorescens), and NP = mixture of 20% phosphate rock and 80% of fresh manure + decomposers + N2-fixer + P-solubilizer. The results showed that inoculation of microbial N2-fixer and combination inoculation of N2-fixer and P-solubilizer increased the total bacterial population compared to that of the control as well as the only inoculation of microbial P-solubilizer on the 14th day of observation in which the bacteria reached the highest population. On all the observation days, the population of fungi in the inoculation of microbial P-solubilizer treatment increased significantly compared to that of the control. However, there was no difference between the populations of fungi in the inoculation of N2-fixer and combination inoculation of N2-fixer and Psolubilizer. The genus of fungy identified in the compost of the mixture of fresh manure and phosphate rock were Chytridium sp., Aspergillus sp., Rhizopus sp., and Fusarium sp.[How to Cite : Nugroho SG, Dermiyati, J Lumbanraja, S Triyono, H Ismono. 2013. Inoculation Effect of N2-Fixer and P-Solubilizer into a Mixture of Fresh Manure and Phosphate Rock Formulated as Organonitrofos Fertilizer on Bacterial and Fungal Populations. J Trop Soils, 18 (1): 75-80. doi: 10.5400/jts.2013.18.1.75][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.75]